Abdominal Incision Selection for Cesarean Delivery of Women with Class III Obesity - Sutton, Amelia L.; Sanders, Lauren B.; Subramaniam, Akila; Jauk, Victoria C.; Edwards, Rodney K. (American Journal of Perinatology, 2016)
Objective The objective of this study was to evaluate cesarean outcomes, stratified by abdominal incision type, in women with class III obesity.Study Design We performed a retrospective cohort study of patients with class III obesity undergoing cesarean at our institution from 2010 to 2013 with singletons ≥ 34 weeks. Outcomes were compared between patients with transverse subpannicular and vertical abdominal incisions. The primary outcome was a wound composite (cellulitis, abscess, hematoma, seroma, or dehiscence). Other outcomes included transfusion, vertical hysterotomy, 5-minute Apgar < 7, and umbilical artery pH < 7.10.Results Of 423 patients, 364 had subpannicular transverse, 57 had vertical, and 2 had periumbilical transverse incisions (not analyzed). Although vertical incisions were associated with more wound complications (26.3 vs. 14.8%; p = 0.03), the difference became null after adjustment (adjusted odds ratios [aOR], 1.7; 95% confidence interval [CI], 0.7, 4.1). Vertical incisions were associated with increased risk of vertical hysterotomy (aOR 4.8; 95% CI, 2.2, 10.4), decreased risk of 5-minute Apgar < 7 (aOR, 0.06; 95% CI, 0.004, 0.9), and not statistically significantly associated with transfusion (aOR, 4.2; 95% CI, 0.9, 19.0) or umbilical artery pH < 7.1 (aOR, 0.42; 95% CI, 0.11, 1.7).Conclusions In women with class III obesity cesarean delivery via vertical abdominal incisions is associated with more maternal but less immediate neonatal complications.
Keywords: cesarean delivery; cesarean; obesity; morbid obesity; incision type